FABRICATING EMPLOYEE ENGAGEMENT FOR ORGANIZATIONAL EFFECTIVENESS: FRAMING ITEMS FOR THE 'CAR-PER-ET-WELL' SCALE - Chauduri, Dr. Manodip Ray; Naskar, Partha (Jurnal Manajemen Indonesia, 2017)
Organization thrive on people. The epicenter of organizational excellence revolves around to the degree and extent of human involvement at work. To have a committed workforce, ensures satisfication, consummation and fulfillment in the minds of employess. A satisfied worker is a happy worker and of course can prove to be most productive, prolific and industrious in his work and in execution of his responsibilities. With a brief introduction on the concept of employess engagement, the paper through detailed literature survey, outlines various aspects of employee engagement, underlying employee career prospects, the significance of ethical framework and significance of employee well-being in the organizational domain. The objective of the paper is to reach understanding of certain identifiable areas within the field of employee engagement viz.; career, performance, ethics and wellness. These issues are quite pertinent for competitive survival of organizations in the current turbulent business climate. A scale "car-per-et-well" has been developed for item analysis in the present study. The coverage of the study makes an attempt to reach out to teh relevance of employee engagement for organizational accomplishment